Psychiatric genetic counseling: A mapping exercise. Issue 8 (20th June 2019) - Moldovan, Ramona; McGhee, Kevin A.; Coviello, Domenico; Hamang, Anniken; Inglis, Angela; Ingvoldstad Malmgren, Charlotta; Johansson‐Soller, Maria; Laurino, Mercy; Meiser, Bettina; Murphy, Lauren; Paneque, Milena; Papsuev, Oleg; et al.
Abstract: Psychiatric genetic counseling (PGC) is gradually developing globally, with countries in various stages of development. In some, PGC is established as a service or as part of research projects while in others, it is just emerging as a concept. In this article, we describe the current global landscape of this genetic counseling specialty and this field's professional development. Drawing on information provided by expert representatives from 16 countries, we highlight the following: (a) current understanding of PGC; (b) availability of services for patients; (c) availability of training; (d) healthcare system disparities and cultural differences impacting practice; and (e) anticipated challenges going forward.